CSF Neurofilament Light Chain Levels in Primary Progressive MS: Signs of Axonal Neurodegeneration - Pawlitzki, Marc; Schreiber, Stefanie; Bittner, Daniel; Kreipe, Julia; Leypoldt, Frank; Rupprecht, Klemens; Carare, Roxana O.; Meuth, Sven G.; Vielhaber, Stefan; Körtvélyessy, Peter (Frontiers in Neurology, 2018)
Objectives: Elevated neurofilament light chain (NFL) levels within the cerebrospinal fluid (CSF) are a biomarker representing axonal neurodegeneration in rapid progressive neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS). It is unclear to what extent the levels of NFL increase in the CSF (CSF-NFL) in a chronic neuroinflammatory process with axonal neurodegeneration, as found in primary progressive multiple sclerosis (PPMS). Methods: We used a multicentre approach to statistically compare CSF-NFL levels between PPMS patients (n = 50), ALS patients (n = 50) and healthy controls (n = 50). Clinical findings, including disease duration, expanded disability status scale (EDSS), electrophysiological recordings such as visual evoked potentials or spinal and cerebral MRI, and previously administered treatment were selected as experimental parameters retrospectively. Results: Median [range] CSF-NFL concentrations in PPMS patients were significantly higher than in the controls (1724 [799-4275] pg/ml vs. 1202 [612-2934] pg/ml, p = 0.015), and significantly lower compared to ALS patients (1724 [799-4275] pg/ml vs. 10238 [2610-35138] pg/ml, p < 0.001). There was no correlation between CSF-NFL and disease duration (p = 0.5), EDSS (p = 0.2) or treatment (p = 0.3). Conclusion: We conclude that CSF-NFL may mirror the proposed slow axonal degeneration in PPMS, but does not reflect the disease severity.